An infant with A20 haploinsufficiency presenting with periodic fever syndrome: A case report. (15th January 2023) - Wakatsuki, Ryosuke; Hatai, Yoshiho; Okamoto, Kentaro; Kaneko, Shuya; Shimbo, Asami; Irabu, Hitoshi; Shimizu, Masaki; Kanegane, Hirokazu; Ono, Makoto
Abstract: A20 haploinsufficiency (HA20) is an early‐onset autoinflammatory disease caused by loss‐of‐function variants of the TNFAIP3 gene, which encodes the protein A20. HA20 is typically characterized by Behçet's disease‐like clinical symptoms, and patients usually present with a family history. Herein, we report a case of HA20 in a pediatric patient, presenting with periodic fever, abdominal pain, and vomiting, with no family history. This patient also harbored a novel heterozygous frameshift variant c.677del (p.Pro226LeufsTer2) of TNFAIP3 . We initiated treatment with an anti‐tumor necrosis factor‐α agent that did not induce symptom resolution; we thus administered combination therapy, including prednisolone. Remission was then successfully achieved. We suggest that HA20 should be considered when an autoinflammatory disease is suspected and periodic fever syndrome is present, even in the absence of a family history of HA20 or Behçet's disease‐like symptoms.